Why do young adults retreat from marriage? An easterlin relative income approach - Georgios Mavropoulos; Theodore Panagiotidis (Comparative Population Studies (CPoS), 2022)
Easterlin's relative income hypothesis refers to the current income of young adults compared to the level of material aspirations acquired during childhood. The hypothesis implies that young individuals are expected to reduce fertility if their material aspirations grow at a higher rate than their incomes. This paper examines whether the same hypothesis holds true for marriage. A higher (lower) level of income combined with a lower (higher) level of material aspirations would increase (decrease) relative income and consequently could affect marriage rates. Thus, relative income might be one explanation for the "marriage paradox" which indicates that young adults in the United States retreat from marriage despite perceiving it as a milestone of their lives. One might also expect relative income to be a better predictor of marriage than absolute income. This is because, according to the Easterlin hypothesis, the behaviour of young adults reflects not only their response to changes in external conditions (e.g. absolute income), but also to past events they have experienced. We employ panel dynamic methods and causality tests for the United States that span the period from 1981 to 2016. Empirical analysis supports the relative income hypothesis. Causality tests indicate that the relationship runs mostly from relative income to marriage rather than the other way round. Relative income emerges as a stronger predictor than absolute income in all of the methods employed.
urn:nbn:de:bib-cpos-2022-03en4
Keywords: 300; Marriage; Relative income; Easterlin hypothesis